How to Support More Flexible Learning Settings in Second Life - Guetl, Christian; Chang, Vanessa; Freudenthaler, S. (Kassel University Press, 2010)
Together with advanced technologies, learning environments in today’s education context are becoming more and more sophisticated. The learning requirements and options for students and instructors are also changing with different types and combination of learning modes (face-to-face, online learning, and blended learning). In addition, students are also located at different geographical regions and these students have to be given the opportunity to choose a mode of learning that suit their lifestyle and location. Virtual 3D Worlds can support such options bytaking advantage of the multiple communication channels and the social engagement associated with presence and awareness. There exist a number of learning settings which are designed for traditional learning approaches that donot support flexible environment. This situation has motivated us to initiate research towards a flexible system which supports configuration and adaptation of virtual learning environment according to the learners’ needs. In this paper, we will present the concept of reuse of resources which were invested to support flexible learning settings. Preliminary findings based on the virtual world Second Life are also discussed.